Determinación de la respuesta agronómica de 20 accesiones de cebada (Hordeum vulgare l.) en su primer año de evaluación, en la zona agro-ecológica de Naguán, parroquia San Lorenzo, cantón Guaranda - Arguello Quintana, Jhony Jesús (2022)
Barley is considered one of the most widely grown cereals in the world, being produced mainly in Russia, France, Germany, Canada, Spain, Turkey, Ukraine, Australia, the United Kingdom and the United States, which have led the world in production. In Ecuador it is grown in the provinces of Chimborazo, Pichincha, Carchi, Cotopaxi and Imbabura. This research was carried out in the agroecological zone of Naguán, belonging to the San Lorenzo parish of the Guaranda canton, located at an altitude of 2652 meters above sea level. The objectives were: i) to identify the morphological characteristics of barley (Hordeum vulgare L.), ii) to evaluate the agronomic characteristics and yield of barley (Hordeum vulgare L.), iii) to select the best materials for this agroecological zone. A randomized complete block design (RCBD) was used, with 20 barley accessions, in 3 replications; analysis of variance, Tukey at 5%, correlation analysis and simple regression were carried out. Assessing the main morphological descriptors, such as the type of straw, 85% of the accessions have a strong and intermediate stem, being materials that can adapt and withstand winds present in the locality; and in the same way in relation to the type and color of grain, it has been possible to identify thick and medium grain with white, cream and yellow main colors, which can have a good demand in the local and national market. Phytosanitation is a fundamental component for the development of an agricultural crop, presenting for the agro-ecological zone of Naguan, a moderate resistance in all the accessions. In relation to the agronomic descriptors, the agronomic response of the accessions, mainly in their yield components, has been highly significant, the treatments with the highest values have been for the INIAP-GUARANGA variety, with 10368 kg/ha, and in second place the promising line CD-18-006 (T2) with 9364 kg/ha; while the lowest average was obtained in the line CD-19-001 (T7), with 4101 kg/ha. The characteristics that negatively affected grain yield were: days to flowering, number of grains per spike, thousand grain weight, and the variables that increased yield were: percentage of grain moisture and hectoliter weight. The statistical data generated in the first validation cycle in the area of Naguán, allow a pre-selection of 10 lines, which showed promising results with a view to the release of new germplasm material for our town and province.